Photodynamic Therapy – In Vitro Investigation Using an Electrochemical Microsensor System. (2015) - Marzioch, J.; Kieninger, J.; Sandvik, J.A.; Pettersen, E.O.; Peng, Q.; Urban, G.
Abstract: A microsensor system to investigate photodynamic therapy of cancer cells in vitro was established. Monitoring of the cellular respiration during and after photodynamic therapy was demonstrated. The system comprises a sensor chip with cell culture chamber, allowing photodynamic treatment by laser light and simultaneous monitoring of metabolic parameter using electrochemical sensors in situ . The sensor chip is integrated into a fluorescence microscope allowing the detection of fluorescence emitted by the photosensitizer as well as to detect fluorescence from additional marker providing optical measurements in parallel to the microsensor readings.